2010
DOI: 10.2174/138920110791233334
|View full text |Cite
|
Sign up to set email alerts
|

Microbattery Technologies for Miniaturized Implantable Medical Devices

Abstract: Implanted medical devices (IMDs), in particular neuro-stimulators, drug delivery chips and cochlear implants are undergoing miniaturization. Some of these miniaturized IMDs are "active" in the sense that they require a power source for operation. In most cases, the ideal power source needs to be an implanted battery of dimensions similar to that of the device. The state-of-the-art of battery miniaturization is reviewed with emphasis on novel Li and Li-ion two- and three-dimensional thin-film microbatteries. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 41 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…Typically, Li batteries were developed and appeared in the forms of Li metal anodes with cathode systems including iodine (Li/I 2 ) [ 2 , 6 , 24 , 63 , 64 ], manganese oxide (Li/MnO 2 ) [ 7 , 12 , 65 , 66 ], carbon mono fluoride (Li/CF x ) [ 67 , 68 , 69 , 70 ], silver vanadium oxide (Li/SVO) [ 71 , 72 , 73 ] or hybrid cathodes (Li/CF x -SVO) [ 29 , 32 , 64 , 74 , 75 ]. As reliable sources for long-term applications such as cochlear implants, pacemakers, cardiac defibrillators or drug delivery, these Li batteries have been widely employed to provide appropriate power levels ranging from microamperes to amperes, as demanded by different types of IMDs [ 26 , 29 , 32 ].…”
Section: Methods To Power Imdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, Li batteries were developed and appeared in the forms of Li metal anodes with cathode systems including iodine (Li/I 2 ) [ 2 , 6 , 24 , 63 , 64 ], manganese oxide (Li/MnO 2 ) [ 7 , 12 , 65 , 66 ], carbon mono fluoride (Li/CF x ) [ 67 , 68 , 69 , 70 ], silver vanadium oxide (Li/SVO) [ 71 , 72 , 73 ] or hybrid cathodes (Li/CF x -SVO) [ 29 , 32 , 64 , 74 , 75 ]. As reliable sources for long-term applications such as cochlear implants, pacemakers, cardiac defibrillators or drug delivery, these Li batteries have been widely employed to provide appropriate power levels ranging from microamperes to amperes, as demanded by different types of IMDs [ 26 , 29 , 32 ].…”
Section: Methods To Power Imdsmentioning
confidence: 99%
“…Since the first medical implant, the pacemaker, was introduced in 1972 using batteries [ 19 , 20 , 21 , 22 , 23 ], various types of batteries have been developed and deployed for IMDs [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Among those, lithium-based (Li) batteries have been the most popular power source owing to their high volumetric energy density as well as comparatively compact sizes [ 28 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Implantable biomedical devices as well as low-power wireless sensor nodes have been demonstrated to function with power consumption in the microwatt range [1], [48], [49]. With the current energy density limits of the lithium-ion battery, a device with 5-μW average power consumption over a 10-year period would require a volume of at least 1 cm 3 [50]. Batteries typically occupy 25 to 60% of the entire device volume [51].…”
Section: Implantable Biomedical Device Applicationsmentioning
confidence: 99%
“…Recent advancements in power supplies for BioMEMS systems demonstrate that it is possible to minimize the power supply components. Conventional methods of supplying electrical power utilize internal Li-ion microbatteries [31]. However, these microbatteries usually occupy a large space in the device, leaving limited space for integrating the other parts into the device.…”
Section: Drug Reservoir Size and Loading Volumementioning
confidence: 99%
“…Recently, several novel approaches have been used to power BioMEMS devices for biological applications. These approaches involve the use of thin film batteries as discussed by Nathan et al [31], wireless power transmission as proposed by Smith et al [49] and battery recharging through the drug refill port as reported by Evans et al [29]. Wireless power transmission has been demonstrated successfully and has a strong potential for powering implantable BioMEMS to increase operation time.…”
Section: Long Operation Timementioning
confidence: 99%